2019
DOI: 10.1002/acr.23622
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Intervention in Primary Care and Rheumatology for the Management of Knee Osteoarthritis: A Review

Abstract: Physical activity (PA) is recommended by osteoarthritis (OA) international organizations as an essential component of first-line management of knee OA. Primary care physicians (PCP) and rheumatologists can play a key role in promoting PA but the extent that PA recommendation is occurring in primary and rheumatology care is unclear. This review provides an overview of current practice of PCP- and rheumatology-delivered PA intervention in the United States, Canada and Europe for the management of knee OA and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The decrease in PT and lifestyle counseling is surprising because promoting physical activity interventions is a front-line approach for knee OA according to most clinical practice guidelines (4,6,7,15,16). The results of our study align with previous reports on OA that suggested an increase in trends of opioid prescriptions (17,18) and a low rate of lifestyle or PT interventions in clinical settings (19,20). The current evidence underscores the need for further investigation to explain why adherence to evidence-based practices is suboptimal and to investigate methods to effectively promote guideline-based care.…”
Section: Discussionsupporting
confidence: 83%
“…The decrease in PT and lifestyle counseling is surprising because promoting physical activity interventions is a front-line approach for knee OA according to most clinical practice guidelines (4,6,7,15,16). The results of our study align with previous reports on OA that suggested an increase in trends of opioid prescriptions (17,18) and a low rate of lifestyle or PT interventions in clinical settings (19,20). The current evidence underscores the need for further investigation to explain why adherence to evidence-based practices is suboptimal and to investigate methods to effectively promote guideline-based care.…”
Section: Discussionsupporting
confidence: 83%
“…For example, in a 2019 review, the majority of studies found that approximately half or fewer providers counseled (defined in the review as advised, recommended, or prescribed) on physical activity for their patients with knee osteoarthritis. 20 In addition, a 2011 study found that 93% of rheumatology providers (rheumatologists, rheumatology nurses, and physical therapists) from the Netherlands reported always/regularly recommending/advising physical activity for their patients with rheumatoid arthritis. 32 While this study is not methodologically identical to the current study and the latter may not be generalizable to health care providers in the US, findings of these 2 studies are reasonably comparable to those of the current study, which found that 57.7% of PCPs always and 98.4% always or sometimes recommend physical activity to their patients with arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…19 Studies of providers show similar results. In a 2019 review, the majority of studies found that less than half of primary care providers (PCPs) and rheumatologists recommended physical activity to their patients with osteoarthritis, and less than half of patients received a recommendation 20 ; the majority of studies in this review were from outside of the US and reported on differences by patient, rather than provider, characteristics. To address these knowledge gaps, this study examined 2 components of physical activity counseling: assessment and recommendation.…”
Section: Purposementioning
confidence: 99%
“…Previous reviews have explored the effects of physical activity interventions in sedentary adults and those with long-term conditions in the primary care setting 25–28. Barriers and facilitators to physical activity and the effectiveness of different modes of delivery have been explored 29–32.…”
Section: Introductionmentioning
confidence: 99%